Evaluation of leishmanicidal effect of Euphorbia erythadenia extract by in vitro leshmanicidal assay using promastigotes of Leishmania major - Reza Kazemi Oskuee; Mahmoud Reza Jaafari; Sara Amani; Mohammad Ramezani (Asian Pacific Journal of Tropical Biomedicine, 2014)
Objective: To evaluate leishmanicidal effects of Euphorbia erythadenia plant extract. Methods: Extraction was done using methanolic Soxhlet of dried and ground aerial parts of the plant. Then, five different extract concentrations, in addition of positive, negative and solvent controls were prepared and added to a 24-well plate containing 40 000 parasites/well. The extract concentrations were 1, 0.5, 0.25, 0.125 and 0.062 5 mg/mL. Amphotricin B (0.5 mg/mL) was used as positive control while negative control contained only culture medium. After 3 d incubation at 25 °C the amount of parasites in each well was determined on each day of experiment microscopially using Neubar chamber. Results: Soxhlet extract as well as amphotricin B killed all parasites at concentration of 1 mg/mL. The leshmanicidal activity of lower doses of extract was dose-dependent. The EC50 for Soxhlet extracts in dimethylsulfoxide was 0.30 mg/mL. The EC50 for Soxhlet extracts in methanol was 0.23 mg/mL. No obvious effects from the control solvent on the Leishmania major promastigotes were observed. Conclusions: The Soxhlet extract of Euphorbia erythadenia showed suitable leishmanicidal activity, especially in higher concentration fractions.